2016
DOI: 10.1016/j.jcrs.2016.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral cataract, crash risk, driving performance, and self-regulation practices among older drivers

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 50 publications
(97 reference statements)
2
20
0
Order By: Relevance
“…Angina, myocardial infarction or coronary disease were associated with the avoidance of driving in heavy traffic, a potentially stressful situation. Consistently with our results, associations with driving self-regulation have been already reported for cataract26 27 and glaucoma 28. People suffering from nephritic colic and urinary stones reported to avoid driving at night, a time when the symptoms of kidney stone emergencies typically begin 29.…”
Section: Discussionsupporting
confidence: 93%
“…Angina, myocardial infarction or coronary disease were associated with the avoidance of driving in heavy traffic, a potentially stressful situation. Consistently with our results, associations with driving self-regulation have been already reported for cataract26 27 and glaucoma 28. People suffering from nephritic colic and urinary stones reported to avoid driving at night, a time when the symptoms of kidney stone emergencies typically begin 29.…”
Section: Discussionsupporting
confidence: 93%
“…As mentioned above, crash rates have been shown to decline in those who have had cataract surgery 1,2,3 , although it is not clear what the objective driving exposure was for the participants examined. If older drivers drive more following surgery, this suggests that their risk for crashing should be increased because their overall exposure is increased.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that they were possibly restricting their driving less after surgery. Previous research has found that older drivers with cataracts self-report at least partly restricting their driving, and several studies have found that drivers self-report fewer difficulties with driving after cataract surgery 1,13 . However, we are not aware of any other studies that have objectively measured driving patterns before and after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations